2018
DOI: 10.1016/j.mec.2018.e00073
|View full text |Cite
|
Sign up to set email alerts
|

Engineering redox-balanced ethanol production in the cellulolytic and extremely thermophilic bacterium, Caldicellulosiruptor bescii

Abstract: Caldicellulosiruptor bescii is an extremely thermophilic cellulolytic bacterium with great potential for consolidated bioprocessing of renewable plant biomass. Since it does not natively produce ethanol, metabolic engineering is required to create strains with this capability. Previous efforts involved the heterologous expression of the gene encoding a bifunctional alcohol dehydrogenase, AdhE, which uses NADH as the electron donor to reduce acetyl-CoA to ethanol. Acetyl-CoA produced from sugar oxidation also g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Further improvements in ethanol titers during the growth on cellulose or xylan were made by introducing a reduced ferredoxin NAD oxidoreductase complex (Rnf) from Thermoanaerobacter sp. X514 [129] into C. bescii, which increased the NADH/NAD + ratio [130].…”
Section: Metabolic Engineeringmentioning
confidence: 97%
“…Further improvements in ethanol titers during the growth on cellulose or xylan were made by introducing a reduced ferredoxin NAD oxidoreductase complex (Rnf) from Thermoanaerobacter sp. X514 [129] into C. bescii, which increased the NADH/NAD + ratio [130].…”
Section: Metabolic Engineeringmentioning
confidence: 97%
“…For industrial biotechnology to achieve an aspirational goal of producing bio‐based fuels and chemicals from renewable feedstocks, significant improvements must be made in the process by which lignocellulose is deconstructed, solubilized, and converted. Many strategies have been pursued along these lines, including the development of transgenic grasses and trees (Biswal et al, ; Zurawski et al, ), physical, chemical, and enzymatic pretreatment of biomass (Kim, Lee, & Kim, ), and isolation and metabolic engineering of microorganisms to enhance complex carbohydrate degradation (Conway et al, ) and fermentation to useful products (Williams‐Rhaesa et al, ). To improve process economics, feedstock‐microbe pairings that require minimal pretreatment are highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The most studied from this genus is Caldicellulosiruptor bescii that cometabolizes five‐carbon (C5) and six‐carbon (C6) sugars (Blumer‐Schuette et al, ), thereby rapidly and extensively converting lignocellulose‐derived complex carbohydrates, such as arabinan (C5), mannan (C6), galactan (C6), xylan (C5), and cellulose (C6), into fermentation products (Zurawski et al, , ). C. bescii has already been engineered to produce ethanol from switchgrass (Chung, Cha, Guss, & Westpheling, ), and further improvements in the genetics toolbox for this bacterium (Lipscomb, Conway, Blumer‐Schuette, Kelly, & Adams, ; Williams‐Rhaesa et al, ) bode well for developing strains with enhanced carbohydrate degradation capacity (Conway et al, ) and increased levels of metabolically engineered products (Williams‐Rhaesa et al, ). The complex structure and content of plant biomass exacerbates the microbial degradation of the carbohydrate content present as cellulose and hemicellulose, even at low biomass loadings.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a variety of thermophilic bacteria and their secreted enzymes have great application potential in bioenergy production and anaerobic fermentation, and these include Caldicellulosiruptor bescii, Geobacillus proteiniphilus, Thermoanaerobacterium, Pyrococcus, and Caldicellulosiruptor (Jiang et al, 2018;Williams-Rhaesa et al, 2018;Semenova et al, 2019;Straub et al, 2019;Hoffmann et al, 2020). Thermophilic Clostridium has been successfully used as green biologics to produce biobutanol using corn stock as a substrate (Zhang and Jia, 2018).…”
Section: Thermophiles and Thermostable Enzymesmentioning
confidence: 99%